Comparison between left bundle branch area pacing and right ventricular pacing: ventricular electromechanical synchrony and risk of atrial high-rate episodes - Yang, Wang-Yang; Di, Bei-Bing; Peng, Hui; Sun, Zhi-Jun (Frontiers in Cardiovascular Medicine, 2024)
The electromechanical dyssynchrony associated with right ventricular pacing (RVP) has been found to have adverse impact on clinical outcomes. Several studies have shown that left bundle branch area pacing (LBBAP) has superior pacing parameters compared with RVP. We aimed to assess the difference in ventricular electromechanical synchrony and investigate the risk of atrial high-rate episodes (AHREs) in patients with LBBAP and RVP.We consecutively identified 40 patients with atrioventricular block and no prior atrial fibrillation. They were divided according to the ventricular pacing sites: the LBBAP group and the RVP group (including the right ventricular apical pacing (RVA) group and the right side ventricular septal pacing (RVS) group). Evaluation of ventricular electromechanical synchrony was implemented using electrocardiogram and two-dimensional speckle tracking echocardiography (2D-STE). AHRE was defined as event with an atrial frequency of ≥176 bpm lasting for ≥ 6 minutes recorded by pacemakers during follow-up.The paced QRS duration of the LBBAP group was significantly shorter than that of the other two groups: LBBAP 113.56±9.66 vs RVA 164.73±14.49 ms, p<0.001; LBBAP 113.56±9.66 vs RVS 148.23±17.3 ms, p<0.001. The LBBAP group showed shorter maximum difference (TDmax), and standard deviation (SD) of the time to peak systolic strain among the 18 left ventricular segments, and time of septal-to-posterior wall motion delay (SPWMD) compared with the RVA group (TDmax, 87.56±56.01 vs 189.85±91.88 ms, p=0.001; SD, 25.40±14.61 vs 67.13±27.40 ms, p<0.001; SPWMD, 28.75±21.89 vs 99.09±46.56 ms, p<0.001) and the RVS group (TDmax, 87.56±56.01 vs 156.46±55.54 ms, p=0.003; SD, 25.40±14.61 vs 49.02±17.85 ms, p=0.001; SPWMD, 28.75±21.89 vs 91.54±26.67 ms, p<0.001). The interventricular mechanical delay (IVMD) was shorter in the LBBAP group compared with the RVA group ( -5.38±9.31 vs 44.82±16.42 ms, p<0.001) and the RVS group (-5.38±9.31 vs 25.31±21.36 ms, p<0.001). During follow-up, 2/16 (12.5%) LBBAP patients, 4/11 (36.4%) RVA patients, and 8/13 (61.5%) RVS patients had recorded novel AHREs. LBBAP was proven to be independently associated with decreased risk of AHREs than RVP (log-rank p=0.043). Conclusion: LBBAP generates narrower paced QRS and better intro-left ventricular and biventricular contraction synchronization compared with traditional RVP. LBBAP was associated with a decreased risk of AHREs compared with RVP.